2017
DOI: 10.1007/s10021-017-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

Stream Resource Gradients Drive Consumption Rates of Supplemental Prey in the Adjacent Riparian Zone

Abstract: Decades of research have revealed the crucial roles of cross-system energy flows (spatial subsidies) in mediating trophic interactions in recipient systems. Food web theory predicts that the responses of subsidized consumers are a key to understanding the net impacts of spatial subsidies on in situ prey/resources of recipient systems. However, less is known about the factors triggering the cascading biotic interactions across coupled ecosystems. Here, we quantify how riverine productivity (donor system) mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…At least, we found that per-capita nutritional quality of A. ishikariana was not better than other benthic TA B L E 3 Summary of likelihood-ratio tests to examine the interaction between taxonomic identity (Taxa, T) and flight directions (i.e., upstream and downstream directions longitudinally along the channel, and moving away from and toward to the channel laterally on abundance and biomass) (Direction, D) dwelling taxa as shown in relatively high C to N ratios although A. ishikariana could supply more food for its greater abundance during mid-summer for the riparian consumers. Previous studies have shown that riparian consumers in riparian zone are dependent on resources provided from the river (Benjamin et al, 2011;Nakano & Murakami, 2001;Paetzold & Tockner, 2005;Terui et al, 2018), with some studies suggesting that the effect size of resource subsidy depends on seasonal context as well as conditions across the boundary (Lafage et al, 2019;Marczak et al, 2007). Our estimates were conducted in the periods extending over mid-summer when terrestrial productivity also tends to maximize, pointing to the possibility that the dependence of recipient consumers on river resources may not be high.…”
Section: Discussionmentioning
confidence: 82%
“…At least, we found that per-capita nutritional quality of A. ishikariana was not better than other benthic TA B L E 3 Summary of likelihood-ratio tests to examine the interaction between taxonomic identity (Taxa, T) and flight directions (i.e., upstream and downstream directions longitudinally along the channel, and moving away from and toward to the channel laterally on abundance and biomass) (Direction, D) dwelling taxa as shown in relatively high C to N ratios although A. ishikariana could supply more food for its greater abundance during mid-summer for the riparian consumers. Previous studies have shown that riparian consumers in riparian zone are dependent on resources provided from the river (Benjamin et al, 2011;Nakano & Murakami, 2001;Paetzold & Tockner, 2005;Terui et al, 2018), with some studies suggesting that the effect size of resource subsidy depends on seasonal context as well as conditions across the boundary (Lafage et al, 2019;Marczak et al, 2007). Our estimates were conducted in the periods extending over mid-summer when terrestrial productivity also tends to maximize, pointing to the possibility that the dependence of recipient consumers on river resources may not be high.…”
Section: Discussionmentioning
confidence: 82%
“…Fish species that did not show any obvious population changes during the period of this study may merit further monitoring over a longer period of time. However, these linkages also propagate unfavorable effects, such as the dispersal of alien species (Atobe, Osada, Takeda, Kuroe, & Miyashita, 2014;Rahel, 2007), pathogens (Jules, Kauffman, Ritts, & Carroll, 2002), and pollutants (Hashimoto et al, 2013;Lebowitz, 2003) and these indirect effects (Paetzold, Smith, Warren, & Maltby, 2011;Terui et al 2018a). Ecosystem linkage greatly affects population productivity and consumer-resource dynamics in the recipient ecosystem of a resource subsidy (Polis, Anderson, & Holt, 1997), and habitat connectivity has important roles in the stability of local populations and the dynamics and structure of local communities (Leibold et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The positive roles of these ecosystem/habitat linkages have been widely discussed (e.g., Baxter, Fausch, & Saunders, 2005;Nakano & Murakami, 2001;Terui et al, 2018b). However, these linkages also propagate unfavorable effects, such as the dispersal of alien species (Atobe, Osada, Takeda, Kuroe, & Miyashita, 2014;Rahel, 2007), pathogens (Jules, Kauffman, Ritts, & Carroll, 2002), and pollutants (Hashimoto et al, 2013;Lebowitz, 2003) and these indirect effects (Paetzold, Smith, Warren, & Maltby, 2011;Terui et al 2018a). It is well known that the top-down effects of large herbivores greatly change terrestrial ecosystems (Côté et al, 2004;Fuller & Gill, 2001;Paine, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Ecological entities rarely exist independently. Dispersal—any movement of organisms across space (Bowler & Benton, 2005)—links populations (Hanski, 1999; Hanski & Ovaskainen, 2000; Terui et al 2014b; Terui et al 2018a), communities (Leibold et al, 2004) and food webs (Nakano, Miyasaka, & Kuhara, 1999; Nakano & Murakami, 2001; Spiller et al, 2010; Terui et al 2018b). Despite the inherent difficulty in quantifying dispersal in the wild (Nathan, 2001), dispersal research has evolved as a major field in ecology and has provided implications for critical applied issues, such as the metapopulation persistence of endangered species in fragmented landscapes (Hanski, 1999).…”
Section: Introductionmentioning
confidence: 99%